A study on emotional maturity and marital status among employees in government sector - Rajkumar, A. (University of Jaffna, 2015)
The Emotional maturity becomes very important in the behavior of people. It is one of the main determining aspects that lead to a successful life. It is shaped by our upbringing and life experiences. Employees are the valuable assets in an organization. Their psychological wellbeing will be affected by several factors including emotionality. The present research investigates the level of Emotional maturity and marital status among employees in Government sector. A random sample consisted of 100 government employees was drawn from the Municipal Council, Jaffna. Standardized scale namely Emotional Maturity Scale designed by Yasvir Singh and Magesh Bhargava was administered to assess the emotional components like emotional instability, emotional regression, social maladjustment, personality disintegration and lack of independence. The collected data were tabulated, processed and analyzed by employing statistical techniques like standard deviation and t test. The results of the study indicated that there is no significant difference in the level of Emotional maturity among employees in Government sector on the basis of marital status. It was also noticed that employees in the government sector are emotionally unstable.
Keywords: Emotional maturity; Emotional stability; Emotional regression; social maladjustment; Government employees